Molecular interaction studies of initial electrostatic attraction between trypsin and the human PAR-2 receptor - Kristoffersen, Tonje Håtveit (UiT Norges arktiske universitet, 2020)
Workers in livestock and fish cultivation are at increased risk of occupational airway damage caused by proteases. Proteases, such as trypsin, activate PAR-2 which in turn triggers an inflammatory response, potentially causing airway damage over time. There has been some speculation that PAR-2 receptors easier attract trypsin form species where this enzyme has a more negative electrostatic charge. A molecular modelling approach was used to assess the initial binding of the activating peptide segment of PAR-2 to trypsin from multiple animal species. Homology modelling was used to predict the structures of Pacific sardine trypsin, yellowtail trypsin and red king crab trypsin, as well as to construct the N-terminal peptide segment of PAR-2. Protein-protein docking was performed to predict initial surface interactions between the PAR-2 peptide segment and trypsin. The binding interaction was mapped, and the interacting amino acids were compared across the species, as well as the charge of the protein binding surfaces. The study indicates that there is, at least, a stronger initial interaction between the N-terminal peptide segment of PAR-2 and trypsin with a stronger negative charge.